Analysis of the financial performance in the Slovenian tourism economy - Planinc, Tanja (Management, 2013)
This paper aims to analyze the difference in financial performance of the different tourism economy activities in Slovenia. The analysis was performed for the period 19952009. We analyzed the financial indicators on the basis of the official company accounts data. The nominal financial data are deflated by the statistical deflator for value of inflation in order to obtain real values of financial indicators over the analyzed years. We included financial indicators that are related to the business performance of enterprises in the Slovenian tourism economy. The research hypothesis was tested using quantitative analysis employing nonparametric Kruskal-Wallis test and Wilcoxon-Mann-Whitney test of the secondary data used. The empirical analysis confirmed that there are significant differences in financial performance among different tourism economy activities in Slovenia.
Keywords: finančno poslovanje; poslovna uspešnost; Slovenia; Slovenija; tourism; turizem